(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The problem of rational and emotional means of art mastering unity is actualized; essence of consolidation unity of cognitive-searching, estimation-interpretative and creative-productive kinds of educational activity of music-pedagogical profile specialists is educated.